2021
DOI: 10.1093/cid/ciab415
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Carbapenemase-Producing Carbapenem-Resistant Enterobacteriaceae Positive Cultures in a Cohort of US Veterans

Abstract: Introduction Carbapenem-resistant Enterobacterales (CRE) cause approximately 13,100 infections with 8% mortality in the United States annually. The subset of carbapenemase-producing CRE (CP-CRE) infections have much higher mortality rates (40% -50%). There has been little research on characteristics unique to CP-CRE. The goal of this study was to assess differences between those with nonCP-CRE and CP-CRE cultures in U.S. Veterans. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Antibiotic susceptibility data for VGS isolates from patients, and their demographic, medical and facility level covariates were obtained retrospectively from VA Medical Centers, as previously described. 11 Streptococcus mitis , Streptococcus oralis and non-speciated VGS isolates with susceptibility data collected between 2010 and 2020 at 122 VA Medical Centers across the United States were included. Susceptibility data originated from testing performed by each VA Medical Center and were pulled from the electronic medical records via the Corporate Data Warehouse.…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic susceptibility data for VGS isolates from patients, and their demographic, medical and facility level covariates were obtained retrospectively from VA Medical Centers, as previously described. 11 Streptococcus mitis , Streptococcus oralis and non-speciated VGS isolates with susceptibility data collected between 2010 and 2020 at 122 VA Medical Centers across the United States were included. Susceptibility data originated from testing performed by each VA Medical Center and were pulled from the electronic medical records via the Corporate Data Warehouse.…”
Section: Methodsmentioning
confidence: 99%
“…This result is similar to the 20.0% CP-CRE-positive rate [17] obtained in a study in patients with CRE admitted to ICUs and transplant wards of a single hospital in the United States. However, it is much lower than the 27.7% [18] reported in a study using a cohort of patients admitted to 127 veterans hospitals in the United States and the 31.5% reported by the US Centers for Disease Control and Prevention' Antibiotic Resistance Laboratory Network [30], and 44.7% of national surveillance report using both active surveillance cultures and clinical samples from 189 institutions in Korea [31]. This result may be related to the difference in the sample mix; colonized by or infected with CRE.…”
Section: Discussionmentioning
confidence: 74%
“…According to previous studies, the positivity rate for CP-CRE differs depending on the CRE-infected or colonized patients varies widely from 20% [17] to 67.9% [18]. CP-CRE-related characteristics also showed different results depending on which of the CREinfected or colonized patients were targeted.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…41 Lastly, the Department of Veterans Affaris demonstrated that among a retrospective cohort of patients with CRE, more persons of White race were identified; however, among the subset with CP-CRE, patients were significantly more likely to be of African American or Black race. 42 A carbapenemase gene was identified in 5 of the 12 CA-CRE isolates that underwent whole genome sequencing at the CDC, KPC being the most commonly identified gene (n = 4). In the United States, acquisition of CRE harboring carbapenemase enzymes is commonly linked to inpatient health care exposures, and among the carbapenemase KPC is the gene most commonly identified.…”
Section: Article In Pressmentioning
confidence: 99%